(untitled) (Research, Society and Development, 2020)
Introduction: mucositis is one of the most common side effects that manifest during chemotherapy treatments against severe cancers. Such treatments have prominent drug 5-Fluorouracil (5-FU). However, patients undergoing anti-cancer treatments that include 5-FU and other cytotoxic drugs in chemotherapy suffer severe side effects. Objectives: the present article aims to assess which is the most promising treatment, in an animal model, to prevent intestinal mucositis induced by 5-FU. Methodology: a digital search was carried out in the main online databases in the health field, such as: “Pubmed”, “BVS”, “ScienceDirect”, “SciELO” and MEDLINE”. The search strategy in all databases was to enter the descriptors “treatment AND intestinal mucositis AND 5-Fluorouracil”. Results: at that time, 191 articles were found. After analyzing the inclusion and exclusion criteria, 51 articles were chosen for a thorough analysis of the methodology and results. As for the analysis parameters of the articles in this review, the following will be included: the methodology used; the possible study biases; and the results obtained from histological, enzymatic, cytosine, and, above all, clinical analyzes. The working groups that used as substances were analyzed: probiotics; phytotherapy; allopathic; selenium and others. Conclusion: it was possible to perceive more promising results in the group of probiotics, especially Bidens pilosa L. (Asteraceae).